Finite element modelling of vibration characteristics of aircraft wing structure - Ong, Han Sheng (2009)
This project provides a theoretical review and investigation of the vibration characteristics of an aircraft wing structure using the Finite Element Method. The vibration characteristics would include its natural frequencies and the different mode shapes of vibrations. The modal analysis was carried out on a computer-generated wing model, modeled after the wing of the A-4SU Super Skyhawk. The wing was created using actual dimensions with Solidworks, after which, the modal analysis was done using Ansys, to extract the first 5 natural frequencies and its corresponding mode shapes. The initial stages of the analysis involved the input of 2 sets of material data to investigate the relationship between material of a solid wing structure and its natural frequency. The results were used to determine the material to be used for subsequent analysis. Following that, a relationship between meshing and the natural frequency was established by the variation of the element size used for meshing. More details were added to the wing model, improving from a solid wing to a hollow wing. This forms the basis of the following analysis, where a comparison of the frequency values was done on both models. The last set of results was obtained by putting the hollow wing under different constraint conditions to investigate how this would affect the vibration characteristics. Simulation results showed that meshing using smaller elements would result in smaller natural frequency values. In addition, over-constraining of the wing would give rise to high frequency values.